(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article considers the responsibility of civil society, experimenting with models of effective global citizenship, as well as deepening the understanding of the characteristics of humanity and the planet, caring for them and acting in their interests on the basis of environmentally responsible and socially inclusive principles and practical steps. Global citizenship is transforming the worlds of art, business, culture, education, human and labor rights, religion, public health, politics, and our relationship with nature